EFEKTIVITAS METODE INSIDE OUTSIDE CIRCLE DALAM MENINGKATKAN KETERAMPILAN KOMUNIKASI SISWA SEKOLAH DASAR - Mitro, Mitro (Fakultas Dharma Acarya IAHN-TP Palangka Raya, 2025)
This research is based on the lack of students' ability to express opinions, especially in Hindu religious education subjects in elementary schools. The aim of this research is to measure the level of effectiveness of the Inside-Outside-Circle (IOC) method in improving students' communication skills. This research is classified as experimental research with pre test post test group design. Communication skills are measured by three indicators, namely Expressing Opinions, Arguing, and Listening. The research results show that the IOC method as a whole is considered effective, with a total N-Gain value of 77.15. In the indicator of conveying opinions, this method produces an N-Gain of 80.08 which is included in the effective category, while for listening it reaches an N-Gain of 77.78, also in the effective category. Although the argued indicator shows quite good improvement with an N-Gain of 73.61, it is in the moderately effective category, which indicates the need for further development. Overall, the IOC method is considered successful in improving students' communication skills, both in expressing opinions, listening and arguing, and can be recommended as an effective method in learning Hindu Religious Education in Elementary Schools.